Plasma Science: Enabling Technology, Sustainability, Security, and Exploration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Plasma Science and Engineering transforms fundamental scientific research into powerful societal applications, from materials processing and healthcare to forecasting space weather. Plasma Science: Enabling Technology, Sustainability, Security and Exploration discusses the importance of plasma research, identifies important grand challenges for the next decade, and makes recommendations on funding and workforce. This publication will help federal agencies, policymakers, and academic leadership understand the importance of plasma research and make informed decisions about plasma science funding, workforce, and research directions.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

The Endless Frontier: The Next 75 Years in Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Academy of Sciences hosted a symposium on February 26, 2020, that gathered top business, academic, and government leaders to explore whether the modern research architecture that fuels U.S. innovation needs to be reconfigured to meet the challenges of our time. The event was held in partnership with The Kavli Foundation and the Alfred P. Sloan Foundation to mark the 75th anniversary of the publication of Vannevar Bush's seminal report Science, the Endless Frontier, which created a blueprint for U.S. scientific research in the post-World War II era. Bush's report empowered government support for innovation and basic research at the nation's universities and the policies that ultimately drove U.S. prosperity, health, and national security. This publication summarizes the presentations and discussion at the symposium focused on the future of pathways to leadership in science, how to respond to changes in the research enterprise, science and the public, the evolution of the government-university partnership, and connecting basic research with economic growth in the decades to come.
Keywords: Policy for Science and Technology

Science Breakthroughs to Advance Food and Agricultural Research by 2030 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
For nearly a century, scientific advances have fueled progress in U.S. agriculture to enable American producers to deliver safe and abundant food domestically and provide a trade surplus in bulk and high-value agricultural commodities and foods. Today, the U.S. food and agricultural enterprise faces formidable challenges that will test its long-term sustainability, competitiveness, and resilience. On its current path, future productivity in the U.S. agricultural system is likely to come with trade-offs. The success of agriculture is tied to natural systems, and these systems are showing signs of stress, even more so with the change in climate. More than a third of the food produced is unconsumed, an unacceptable loss of food and nutrients at a time of heightened global food demand. Increased food animal production to meet greater demand will generate more greenhouse gas emissions and excess animal waste. The U.S. food supply is generally secure, but is not immune to the costly and deadly shocks of continuing outbreaks of food-borne illness or to the constant threat of pests and pathogens to crops, livestock, and poultry. U.S. farmers and producers are at the front lines and will need more tools to manage the pressures they face. Science Breakthroughs to Advance Food and Agricultural Research by 2030 identifies innovative, emerging scientific advances for making the U.S. food and agricultural system more efficient, resilient, and sustainable. This report explores the availability of relatively new scientific developments across all disciplines that could accelerate progress toward these goals. It identifies the most promising scientific breakthroughs that could have the greatest positive impact on food and agriculture, and that are possible to achieve in the next decade (by 2030).
Keywords: Agriculture; Food and Nutrition; Earth Sciences; Environment and Environmental Studies

Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Children are the foundation of the United States, and supporting them is a key component of building a successful future. However, millions of children face health inequities that compromise their development, well-being, and long-term outcomes, despite substantial scientific evidence about how those adversities contribute to poor health. Advancements in neurobiological and socio-behavioral science show that critical biological systems develop in the prenatal through early childhood periods, and neurobiological development is extremely responsive to environmental influences during these stages. Consequently, social, economic, cultural, and environmental factors significantly affect a child's health ecosystem and ability to thrive throughout adulthood. Vibrant and Healthy Kids: Aligning Science, Practice, and Policy to Advance Health Equity builds upon and updates research from Communities in Action: Pathways to Health Equity (2017) and From Neurons to Neighborhoods: The Science of Early Childhood Development (2000). This report provides a brief overview of stressors that affect childhood development and health, a framework for applying current brain and development science to the real world, a roadmap for implementing tailored interventions, and recommendations about improving systems to better align with our understanding of the significant impact of health equity.
Keywords: Health and Medicine; Education

Strengthening Sustainability Programs and Curricula at the Undergraduate and Graduate Levels - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Over the past decade there has been a growing interest in sustainability education in colleges and universities across the United States, with a marked increase in the number of undergraduate and graduate degree programs, research institutes, and centers focused on sustainability. Evidence-based core competencies for interdisciplinary sustainability programs can provide suitable guidance for curricular and program development, research, policy, communication, and pedagogical approaches at academic institutions. They can also serve as a guide for students to select academic programs and potential career options, a reference for employers to understand qualifications of graduates, and the foundation for a potential specialized accreditation for interdisciplinary sustainability programs. The growing demand for well-qualified sustainability professionals within the public, private, and nonprofit sectors also points to the value of developing core competencies. Strengthening Sustainability Programs and Curricula at the Undergraduate and Graduate Levels provides expert insights for strengthening the emerging discipline of sustainability in higher education in the United States. This report describes the local, national, and global landscape related to sustainability education; examines the history and current status of sustainability education programs in the United States and globally; discusses employment prospects for sustainability graduates in terms of the opportunities and the skills that employers seek; and addresses diversity, equity, and inclusion in sustainability-related education and employment.
Keywords: Education

Frontiers of Materials Research: A Decadal Survey - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Modern materials science builds on knowledge from physics, chemistry, biology, mathematics, computer and data science, and engineering sciences to enable us to understand, control, and expand the material world. Although it is anchored in inquiry-based fundamental science, materials research is strongly focused on discovering and producing reliable and economically viable materials, from super alloys to polymer composites, that are used in a vast array of products essential to today's societies and economies. Frontiers of Materials Research: A Decadal Survey is aimed at documenting the status and promising future directions of materials research in the United States in the context of similar efforts worldwide. This third decadal survey in materials research reviews the progress and achievements in materials research and changes in the materials research landscape over the last decade; research opportunities for investment for the period 2020-2030; impacts that materials research has had and is expected to have on emerging technologies, national needs, and science; and challenges the enterprise may face over the next decade.
Keywords: Engineering and Technology

Manipulating Quantum Systems: An Assessment of Atomic, Molecular, and Optical Physics in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The field of atomic, molecular, and optical (AMO) science underpins many technologies and continues to progress at an exciting pace for both scientific discoveries and technological innovations. AMO physics studies the fundamental building blocks of functioning matter to help advance the understanding of the universe. It is a foundational discipline within the physical sciences, relating to atoms and their constituents, to molecules, and to light at the quantum level. AMO physics combines fundamental research with practical application, coupling fundamental scientific discovery to rapidly evolving technological advances, innovation and commercialization. Due to the wide-reaching intellectual, societal, and economical impact of AMO, it is important to review recent advances and future opportunities in AMO physics. Manipulating Quantum Systems: An Assessment of Atomic, Molecular, and Optical Physics in the United States assesses opportunities in AMO science and technology over the coming decade. Key topics in this report include tools made of light; emerging phenomena from few- to many-body systems; the foundations of quantum information science and technologies; quantum dynamics in the time and frequency domains; precision and the nature of the universe, and the broader impact of AMO science.
Keywords: Math, Chemistry, and Physics

Safeguarding the Bioeconomy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Research and innovation in the life sciences is driving rapid growth in agriculture, biomedical science, information science and computing, energy, and other sectors of the U.S. economy. This economic activity, conceptually referred to as the bioeconomy, presents many opportunities to create jobs, improve the quality of life, and continue to drive economic growth. While the United States has been a leader in advancements in the biological sciences, other countries are also actively investing in and expanding their capabilities in this area. Maintaining competitiveness in the bioeconomy is key to maintaining the economic health and security of the United States and other nations. Safeguarding the Bioeconomy evaluates preexisting and potential approaches for assessing the value of the bioeconomy and identifies intangible assets not sufficiently captured or that are missing from U.S. assessments. This study considers strategies for safeguarding and sustaining the economic activity driven by research and innovation in the life sciences. It also presents ideas for horizon scanning mechanisms to identify new technologies, markets, and data sources that have the potential to drive future development of the bioeconomy.
Keywords: Biology and Life Sciences

Biological Collections: Ensuring Critical Research and Education for the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Biological collections are a critical part of the nation's science and innovation infrastructure and a fundamental resource for understanding the natural world. Biological collections underpin basic science discoveries as well as deepen our understanding of many challenges such as global change, biodiversity loss, sustainable food production, ecosystem conservation, and improving human health and security. They are important resources for education, both in formal training for the science and technology workforce, and in informal learning through schools, citizen science programs, and adult learning. However, the sustainability of biological collections is under threat. Without enhanced strategic leadership and investments in their infrastructure and growth many biological collections could be lost. Biological Collections: Ensuring Critical Research and Education for the 21st Century recommends approaches for biological collections to develop long-term financial sustainability, advance digitization, recruit and support a diverse workforce, and upgrade and maintain a robust physical infrastructure in order to continue serving science and society. The aim of the report is to stimulate a national discussion regarding the goals and strategies needed to ensure that U.S. biological collections not only thrive but continue to grow throughout the 21st century and beyond.
Keywords: Biology and Life Sciences

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Cultivating Interest and Competencies in Computing: Authentic Experiences and Design Factors - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Computing in some form touches nearly every aspect of day to day life and is reflected in the ubiquitous use of cell phones, the expansion of automation into many industries, and the vast amounts of data that are routinely gathered about people's health, education, and buying habits. Computing is now a part of nearly every occupation, not only those in the technology industry. Given the ubiquity of computing in both personal and professional life, there are increasing calls for all learners to participate in learning experiences related to computing including more formal experiences offered in schools, opportunities in youth development programs and after-school clubs, or self-initiated hands-on experiences at home. At the same time, the lack of diversity in the computing workforce and in programs that engage learners in computing is well-documented. It is important to consider how to increase access and design experiences for a wide range of learners. Authentic experiences in STEM - that is, experiences that reflect professional practice and also connect learners to real-world problems that they care about - are one possible approach for reaching a broader range of learners. These experiences can be designed for learners of all ages and implemented in a wide range of settings. However, the role they play in developing youths' interests, capacities, and productive learning identities for computing is unclear. There is a need to better understand the role of authentic STEM experiences in supporting the development of interests, competencies, and skills related to computing. Cultivating Interest and Competencies in Computing examines the evidence on learning and teaching using authentic, open-ended pedagogical approaches and learning experiences for children and youth in grades K-12 in both formal and informal settings. This report gives particular attention to approaches and experiences that promote the success of children and youth from groups that are typically underrepresented in computing fields. Cultivating Interest and Competencies in Computing provides guidance for educators and facilitators, program designers, and other key stakeholders on how to support learners as they engage in authentic learning experiences.
Keywords: Education; Computers and Information Technology

Climate Change: Evidence and Causes: Update 2020 (The National Academies Press, 2020)
Climate change is one of the defining issues of our time. It is now more certain than ever, based on many lines of evidence, that humans are changing Earth's climate. The Royal Society and the US National Academy of Sciences, with their similar missions to promote the use of science to benefit society and to inform critical policy debates, produced the original Climate Change: Evidence and Causes in 2014. It was written and reviewed by a UK-US team of leading climate scientists. This new edition, prepared by the same author team, has been updated with the most recent climate data and scientific analyses, all of which reinforce our understanding of human-caused climate change. Scientific information is a vital component for society to make informed decisions about how to reduce the magnitude of climate change and how to adapt to its impacts. This booklet serves as a key reference document for decision makers, policy makers, educators, and others seeking authoritative answers about the current state of climate-change science.
Keywords: Environment and Environmental Studies

The Future of Electric Power in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Electric power is essential for the lives and livelihoods of all Americans, and the need for electricity that is safe, clean, affordable, and reliable will only grow in the decades to come. At the request of Congress and the Department of Energy, the National Academies convened a committee of experts to undertake a comprehensive evaluation of the U.S. grid and how it might evolve in response to advances in new energy technologies, changes in demand, and future innovation. The Future of Electric Power in the United States presents an extensive set of policy and funding recommendations aimed at modernizing the U.S. electric system. The report addresses technology development, operations, grid architectures, and business practices, as well as ways to make the electricity system safe, secure, sustainable, equitable, and resilient.
Keywords: Energy and Energy Conservation

English Learners in STEM Subjects: Transforming Classrooms, Schools, and Lives - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The imperative that all students, including English learners (ELs), achieve high academic standards and have opportunities to participate in science, technology, engineering, and mathematics (STEM) learning has become even more urgent and complex given shifts in science and mathematics standards. As a group, these students are underrepresented in STEM fields in college and in the workforce at a time when the demand for workers and professionals in STEM fields is unmet and increasing. However, English learners bring a wealth of resources to STEM learning, including knowledge and interest in STEM-related content that is born out of their experiences in their homes and communities, home languages, variation in discourse practices, and, in some cases, experiences with schooling in other countries. English Learners in STEM Subjects: Transforming Classrooms, Schools, and Lives examines the research on ELs' learning, teaching, and assessment in STEM subjects and provides guidance on how to improve learning outcomes in STEM for these students. This report considers the complex social and academic use of language delineated in the new mathematics and science standards, the diversity of the population of ELs, and the integration of English as a second language instruction with core instructional programs in STEM.
Keywords: Education

Quantum Computing: Progress and Prospects - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Quantum mechanics, the subfield of physics that describes the behavior of very small (quantum) particles, provides the basis for a new paradigm of computing. First proposed in the 1980s as a way to improve computational modeling of quantum systems, the field of quantum computing has recently garnered significant attention due to progress in building small-scale devices. However, significant technical advances will be required before a large-scale, practical quantum computer can be achieved. Quantum Computing: Progress and Prospects provides an introduction to the field, including the unique characteristics and constraints of the technology, and assesses the feasibility and implications of creating a functional quantum computer capable of addressing real-world problems. This report considers hardware and software requirements, quantum algorithms, drivers of advances in quantum computing and quantum devices, benchmarks associated with relevant use cases, the time and resources required, and how to assess the probability of success.
Keywords: Computers and Information Technology

Understanding the Long-Term Evolution of the Coupled Natural-Human Coastal System: The Future of the U.S. Gulf Coast - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The U.S. Gulf Coast provides a valuable setting to study deeply connected natural and human interactions and feedbacks that have led to a complex, interconnected coastal system. The physical landscape in the region has changed significantly due to broad-scale, long-term processes such as coastal subsidence and river sediment deposition as well as short-term episodic events such as hurricanes. Modifications from human activities, including building levees and canals and constructing buildings and roads, have left their own imprint on the natural landscape. This coupled natural-human coastal system and the individual aspects within it (physical, ecological, and human) are under increased pressure from accelerating environmental stressors such as sea level rise, intensifying hurricanes, and continued population increase with its accompanying coastal development. Promoting the resilience and maintaining the habitability of the Gulf Coast into the future will need improved understanding of the coupled natural-human coastal system, as well as effective sharing of this understanding in support of decision-making and policies. Understanding the Long-term Evolution of the Coupled Natural-Human Coastal System presents a research agenda meant to enable a better understanding of the multiple and interconnected factors that influence long-term processes along the Gulf Coast. This report identifies scientific and technical gaps in understanding the interactions and feedbacks between human and natural processes, defines essential components of a research and development program in response to the identified gaps, and develops priorities for critical areas of research.
Keywords: Earth Sciences; Environment and Environmental Studies

Framing the Challenge of Urban Flooding in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Flooding is the natural hazard with the greatest economic and social impact in the United States, and these impacts are becoming more severe over time. Catastrophic flooding from recent hurricanes, including Superstorm Sandy in New York (2012) and Hurricane Harvey in Houston (2017), caused billions of dollars in property damage, adversely affected millions of people, and damaged the economic well-being of major metropolitan areas. Flooding takes a heavy toll even in years without a named storm or event. Major freshwater flood events from 2004 to 2014 cost an average of $9 billion in direct damage and 71 lives annually. These figures do not include the cumulative costs of frequent, small floods, which can be similar to those of infrequent extreme floods. Framing the Challenge of Urban Flooding in the United States contributes to existing knowledge by examining real-world examples in specific metropolitan areas. This report identifies commonalities and variances among the case study metropolitan areas in terms of causes, adverse impacts, unexpected problems in recovery, or effective mitigation strategies, as well as key themes of urban flooding. It also relates, as appropriate, causes and actions of urban flooding to existing federal resources or policies.
Keywords: Earth Sciences

Promoting the Educational Success of Children and Youth Learning English: Promising Futures - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Educating dual language learners (DLLs) and English learners (ELs) effectively is a national challenge with consequences both for individuals and for American society. Despite their linguistic, cognitive, and social potential, many ELs—who account for more than 9 percent of enrollment in grades K-12 in U.S. schools—are struggling to meet the requirements for academic success, and their prospects for success in postsecondary education and in the workforce are jeopardized as a result. Promoting the Educational Success of Children and Youth Learning English: Promising Futures examines how evidence based on research relevant to the development of DLLs/ELs from birth to age 21 can inform education and health policies and related practices that can result in better educational outcomes. This report makes recommendations for policy, practice, and research and data collection focused on addressing the challenges in caring for and educating DLLs/ELs from birth to grade 12.
Keywords: Education; Behavioral and Social Sciences

Shaping Summertime Experiences: Opportunities to Promote Healthy Development and Well-Being for Children and Youth - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
For children and youth, summertime presents a unique break from the traditional structure, resources, and support systems that exist during the school year. For some students, this time involves opportunities to engage in fun and enriching activities and programs, while others face additional challenges as they lose a variety of supports, including healthy meals, medical care, supervision, and structured programs that enhance development. Children that are limited by their social, economic, or physical environments during the summer months are at higher risk for worse academic, health, social and emotional, and safety outcomes. In contrast, structured summertime activities and programs support basic developmental needs and positive outcomes for children and youth who can access and afford these programs. These discrepancies in summertime experiences exacerbate pre-existing academic inequities. While further research is needed regarding the impact of summertime on developmental domains outside of the academic setting, extensive literature exists regarding the impact of summertime on academic development trajectories. However, this knowledge is not sufficiently applied to policy and practice, and it is important to address these inequalities. Shaping Summertime Experiences examines the impact of summertime experiences on the developmental trajectories of school-age children and youth across four areas of well-being, including academic learning, social and emotional development, physical and mental health, and health-promoting and safety behaviors. It also reviews the state of science and available literature regarding the impact of summertime experiences. In addition, this report provides recommendations to improve the experiences of children over the summertime regarding planning, access and equity, and opportunities for further research and data collection.
Keywords: Behavioral and Social Sciences

Forest Health and Biotechnology: Possibilities and Considerations - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The American chestnut, whitebark pine, and several species of ash in the eastern United States are just a few of the North American tree species that have been functionally lost or are in jeopardy of being lost due to outbreaks of pathogens and insect pests. New pressures in this century are putting even more trees at risk. Expanded human mobility and global trade are providing pathways for the introduction of nonnative pests for which native tree species may lack resistance. At the same time, climate change is extending the geographic range of both native and nonnative pest species. Biotechnology has the potential to help mitigate threats to North American forests from insects and pathogens through the introduction of pest-resistant traits to forest trees. However, challenges remain: the genetic mechanisms that underlie trees' resistance to pests are poorly understood; the complexity of tree genomes makes incorporating genetic changes a slow and difficult task; and there is a lack of information on the effects of releasing new genotypes into the environment. Forest Health and Biotechnology examines the potential use of biotechnology for mitigating threats to forest tree health and identifies the ecological, economic, and social implications of deploying biotechnology in forests. This report also develops a research agenda to address knowledge gaps about the application of the technology.
Keywords: Environment and Environmental Studies; Biology and Life Sciences